ARSITEKTUR, MATERIAL BANGUNAN DAN KEHARMONISAN KEHIDUPAN - Prasetiyo, Andi (Talenta Publisher, 2018)
Architecture is not only focused on the physical stucture, but it contains many things that can be synergized, including nature and culture. That synergies were expected to create a work of architecture that is familiar and acceptable. From this premise, the term of eco-architecture known, that will help us create environmentally architectural masterpiece. There were Romo Mangun and Eko Prawoto that give us an understanding on how the architect and their work can be closer to nature and local cultures that exist in the location where the architect is putting their work. This works maybe not using building materials that are super luxurious and high tech. However, from the simplicity born an architectural works that have a 'soul'. Similarly as we as human beings, adapting the architecture to the environment will make the architecture may survive. Harmony of life will be created when the environment and architecture walk in harmony, coexistence and also mutual respect to each other. Architecture is not only focused on the physical stucture, but it contains many things that can be synergized, including nature and culture. That synergies were expected to create a work of architecture that is familiar and acceptable. From this premise, the term of eco-architecture known, that will help us create environmentally architectural masterpiece. There were Romo Mangun and Eko Prawoto that give us an understanding on how the architect and their work can be closer to nature and local cultures that exist in the location where the architect is putting their work. This works maybe not using building materials that are super luxurious and high tech. However, from the simplicity born an architectural works that have a 'soul'. Similarly as we as human beings, adapting the architecture to the environment will make the architecture may survive. Harmony of life will be created when the environment and architecture walk in harmony, coexistence and also mutual respect to each other.